Solid porous microsphere: emerging trend in pharmaceutical technology - KIRTI DESHMUKH; SUSHILKUMAR S. PODDAR (International Journal of Pharma and Bio Sciences, 2011)
SPMs are at the forefront of the rapidly developing field of novel drug delivery technology and tissue engineering technology. This technology holds a great promise for reaching the goal of controlled and site-specific drug delivery and hence, have attracted wide attention of researchers. This review presents a broad treatment of SPMs delivery system discussing the principles and preparation methods. Appropriate analytical techniques for characterization of SPMs like Particle size and its distribution, surface morphology, porosity, density etc are covered. Advantages, limitations and their possible remedies of the MDS are also mentioned. The aspect of route of administration and release mechanisms are also touched upon. If appropriately investigated, SPMs may navigate into new vistas in the therapy of complex diseases and also new opportunities for biomaterial designs for bone related repair, vascular grafts and implants.